Dispositional mindfulness and mental health among Chinese college students during the COVID-19 lockdown: The mediating role of self-compassion and the moderating role of gender - Zhang, Dan; Shen, Jianbo (Frontiers in Psychology, 2023)
College students’ mental health has been seriously impacted during the global COVID-19 lockdown. There is evidence that dispositional mindfulness is beneficial to mental health. However, few studies have looked at the relationship between dispositional mindfulness and mental health from the standpoint of self-compassion. Furthermore, it is unclear under what circumstances dispositional mindfulness is linked to mental health during COVID-19 lockdown. To fill this gap, the current study investigated self-compassion as a possible mediating factor and gender as a possible moderating effect between dispositional mindfulness and mental health. The sample included 1,018 Chinese university students during the COVID-19 lockdown (M age = 20.12; SD age = 1.17) who had completed self-report questionnaires on dispositional mindfulness, self-compassion, and mental health. According to the findings of mediation analysis, self-compassion partially mediated the relationship between dispositional mindfulness and mental health. The moderating analysis also revealed significant moderating effects of dispositional mindfulness, self-compassion, and mental health. Male college students’ mental health was significantly better protected, and the buffering effects of dispositional mindfulness and self-compassion on their mental health were significantly stronger than those of female college students. These findings advance our understanding of the process and mechanism between dispositional mindfulness and mental health, broadened and deepened the understanding of the relationship between dispositional mindfulness and mental health, as well as the mediating role of self-compassion and the moderating role of gender, and offer practical guidance for improving college students’ mental health during the COVID-19 lockdown.